2007
DOI: 10.1080/15569520701588780
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Epithelial Testing Strategies for Safety Evaluation of Ophthalmic Formulations

Abstract: The toxicity of an ophthalmic formulation was tested both in vivo and in vitro. Initial tests on transformed human corneal epithelial (HCE-T) cells in monolayer cultures resulted in adverse effects on cell morphology. The adverse effects were unexpected since the formulation caused no damage to the cornea in vivo. These results suggested HCE-T monolayers do not adequately model the intact corneal epithelium. Therefore, further in vitro studies were conducted to investigate reversibility of morphologic changes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The reason for this lack of a detectable dose response is unknown at this time; however, several reasonable hypotheses may be proposed. First, a difference between monolayer and stratified cells was not unexpected since we have previously reported that more highly differentiated, stratified corneal epithelial cells in culture are less susceptible to damage in toxicologic studies than monolayer cultures (Hoffman et al, 2007; Lim et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The reason for this lack of a detectable dose response is unknown at this time; however, several reasonable hypotheses may be proposed. First, a difference between monolayer and stratified cells was not unexpected since we have previously reported that more highly differentiated, stratified corneal epithelial cells in culture are less susceptible to damage in toxicologic studies than monolayer cultures (Hoffman et al, 2007; Lim et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, HCE-T monolayer cultures have been found to exhibit cytotoxicity when exposed to concentrations of detergents well below those affecting the viability of 3-D cultures [ 17 ]. Furthermore, an ophthalmic solution that was nontoxic in rabbit corneas and 3-D cultures was shown to cause breakage of cell junctions and vacuolization in HCE-T monolayers [ 19 ]. These studies suggest that HCE-T monolayer cultures are not appropriate for evaluating the cytotoxicity of ophthalmic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of exposure of 3-D cultures to test compounds in other studies has varied widely among researchers, with some using 5-minute exposures [ 13 , 17 ] and others using 20- and 60-minute exposures [ 19 ]. In one study demonstrating toxicity of BAC in 3-D cultures at concentrations as low as 0.005%, exposure times were an extraordinarily long 6 and 24 hours [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased sensitivity to cell damage in stratified cultures compared with monolayer cultures is in agreement with the findings of the previous studies of lens care solutions and lubricant eye drops using the HCLE cell line and an SV-40 transformed corneal epithelial cell line, respectively. 17,18 The stratified model seems to be more predictive of the responses to ophthalmic formulations because of its greater anatomic and physiologic similarity to the intact corneal epithelium. This study of H 2 O 2 allows for a comparison between the results of experiments using our in vitro methods and past in vivo or clinical FIG.…”
Section: Discussionmentioning
confidence: 98%
“…The secondary goals of this study were to further evaluate the utility of a battery of in vitro cytotoxicity tests and to obtain additional evidence for our previous observations concerning differences in responses of stratified cultures compared with monolayer cultures that may overly predict damage to the corneal epithelium. 17 concentration was confirmed by laboratory assay conducted at Alcon. The effects of these test formulations were compared with those of Clear Care Ò (CIBA Vision), a peroxide-based contact lens-disinfecting system.…”
mentioning
confidence: 99%